Rheumatoid Meningoencephalitis: A Feared Condition in the Era of TNF Blockers - Fernando Figueroa Rodriguez; Kwon Minkyung; Sruthi Jinna; Sohail Farshad; Francisco Davila (Case Reports in Rheumatology)
Central nervous system (CNS) involvement in rheumatoid arthritis (RA) is uncommon, and most of the times, it is secondary to vasculitic processes or extra-articular rheumatoid nodules. Meningeal involvement is extremely rare. In the literature, there are a few case reports, series, and retrospective studies which have demonstrated the association of rheumatoid (aseptic) meningoencephalitis after starting tumor necrosis factor (TNF) inhibitors. We present a case of rheumatoid meningoencephalitis (RME) in a 52-year-old male with a history of RA on adalimumab who presented with headaches associated with motor and sensory deficits, all of which resolved after this diagnosis was achieved and received appropriate therapy with high-dose glucocorticoids. We also present an update with high yield points summarizing clinical features, diagnostic workup, and management of RME. Finally, we post a literature review of relevant CNS rheumatoid disease in patients with and without exposure to TNF inhibitors.